Correlation Between Intraoperative Blood Vessel Diameter and Technical Success Rate of AV Shunt Surgery in Dr. Soetomo Hospital Surabaya - Saphira, Diva; Soebroto, Heroe; Thaha, Mochammad; Hakim, Arief Rakhman; Widipriyatama, Gabriel Rio (Indonesian Vascular Access Association (IVAA), 2023)
Introduction: An arteriovenous (AV) shunt is an anastomosis between vein and artery made in a surgical procedure as vascular access for patients with end-stage renal disease that are projected to undergo hemodialysis. Unfortunately, AV shunt failure remains a significant clinical problem for hemodialysis patients. In general, the cause of most early AV shunt failure is still unknown, but the quality of the blood vessels is suspected as a factor. This study aimed to determine the correlation between blood vessel diameter and the success of AV shunt surgery. Methods: This study is a cross sectional study that uses a descriptive-analytic design. The samples were obtained from the patient’s medical records with the total sampling technique of all patients who have undergone AV shunt surgery from January 2019 – December 2020 at Dr. Soetomo General Hospital which matches the inclusion and exclusion criteria. Results: Patients’ blood vessel diameter measurement is divided into four categories which are <2 mm, 2 - <4 mm, 4 - <6 mm, and ≥6 mm. From a total of 62 patients, the highest successful surgery rate is carried out in patients with a vein diameter of 2 - <4 mm (77.59%) and artery diameter of 2 - <4 mm (63.79%). The results of the Chi-Square analysis found no significant correlation between vein diameter (p=0.769) or artery diameter (p=0.922) and the success of AV shunt surgery at Dr. Soetomo Hospital, Surabaya 2019-2020. Conclusions: In conclusion, this study did not find a correlation between the intraoperative blood vessel diameter and the technical success of AV shunt surgery.